2007
DOI: 10.2109/jcersj.115.264
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxations in the Ce1-xSmxO2-.DELTA. System

Abstract: Dielectric relaxations were investigated for the solid-solution system Ce 1 x Sm x O 2 d 0.0x0.5 , which is a typical oxide-ion conductor. The dielectric constants showed anomalously large values at low frequencies and high temperatures. Computer simulation clarified that the anomalously large dielectric constant e r ö originated from the superimposition of both Debye-type polarization and interfacial polarization between electrolyte and electrode. Two kinds of Debye-type relaxation observed were ascribed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The relative dielectric constant implied by the high frequency arc is 59 (250 1C, dry) consistent with its assignment as the bulk response; 22,24,[26][27][28] reported values for doped ceria range from approximately 20 to 70. 22,29,30 The effective, relative dielectric constant implied by the mid-frequency arc is 1.8 Â 10 4 , a value that is consistent with grain boundary properties. In contrast, that of the low frequency (electrode) arc is 8.3 Â 10 5 .…”
Section: Transport Under Oxidizing Conditionsmentioning
confidence: 57%
“…The relative dielectric constant implied by the high frequency arc is 59 (250 1C, dry) consistent with its assignment as the bulk response; 22,24,[26][27][28] reported values for doped ceria range from approximately 20 to 70. 22,29,30 The effective, relative dielectric constant implied by the mid-frequency arc is 1.8 Â 10 4 , a value that is consistent with grain boundary properties. In contrast, that of the low frequency (electrode) arc is 8.3 Â 10 5 .…”
Section: Transport Under Oxidizing Conditionsmentioning
confidence: 57%
“…As the present authors indicated in the study of the dielectric properties in the Ca-doped CeO 2 system, the two types of the associates in the fluorite-type structure can originate from the interaction between Y Zr and the nearest oxygen vacancy with r Y VO 0.43a o , and the second nearest oxygen vacancy with r Y VO 0.90a o , where a o represents the lattice constant of the fluorite structure. 12 On the other hand, the high frequency relaxation would be ascribed to the oxideion migration, because it has extremely small dielectric constant, and it appeared at high frequency region in spite of low temperature. This speculation agreed with the analysis of M ÷ in the La-or Y-doped CeO 2 system after Sarker and does not show the dipole moment due to the electrical neutrality of Zr Zr .…”
Section: Dielectric Relaxations Of Y-doped Zro 2 Single Crystalmentioning
confidence: 99%
“…Eq. (6) suggests that the subtraction of the second term in the right hand side of the equation from ε r will give the value of dielectric loss due to the dipoles and produce the loss in ε r due to Debye-type relaxation [13]. Fig.…”
Section: Complex Dielectric Formalismmentioning
confidence: 99%
“…Oxide ion conduction gets influenced by defect associates. The associates act as dipoles which are responsible for dielectric relaxation, when subjected to an ac electric filed [6]. These dipoles are responsible for charge storage inside the material, thereby leading to high dielectric constant.…”
Section: Introductionmentioning
confidence: 99%